Colonial governmentality and the native intellectual response: Cultural plurality, imperial education and the foundations of democratic governance in modern south Asia - Kumar, Sanjeev H.M. (Indian Journal of Public Administration)
This article is premised on the argument that the idea of modern South Asia has been a product of the transformation of the region$1 (Bs identity from being an exemplar of a cohesive macro-cultural topography in the ancient world to becoming an incohesive social formation today. Such a transformation was impelled by the epistemic rupture that it experienced, owing to the coming of the values of post-Enlightenment Modernity after the advent of the era of colonial transition. However, the emergence of the idea of South Asia, which is inherent with deep-seated sociocultural cleavages, cannot merely be explained by according a singular monovalent emphasis on the role of imported values of European Enlightenment. Rather, it is crucial to locate such a transformation in the context of the contribution of the native intellectual response to the arrival of the values of European Enlightenment. Situating ourselves in this epistemic framework, this article argues that the structuration processes which produced a fractured social cartography in modern South Asia have been a creation of the dialectical epistemic interaction between the forms of colonial knowledge and the native intellectual responses.- Reproduced s
Keywords: Colonial knowledge, Colonial governmentality, Colonial historiography, European enlightenment, Democratic governance, Modern South Asia